PENGARUH PENGEMBANGAN KARIR DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN DI CV. DANAGUNG D’ BRIQUETTESS BANTUL YOGYAKARTA - Amaliya Dwi Anjani (Program Studi Manajemen Fakultas Ekonomi UST, 2022)
The purpose of the research is to describe the effect of career development and self efficacy on the performance of employees of CV. Danagung D'briquetess Bntul Yogyakarta. This method of study uses saturated samples due to the small number of populations in the company. Data collection techniques using the questionnaire distributed through the company owner. Data analysis techniques using SPSS application version 20 include quality test, classic assumption test, multiple linear regression test, and coefficient of determination.. the study found that the career development and Self Efficacy variables have positive and significant impact on employee performance. The most dominant influence is self efficacy is followed by career development.